Human integrity and gene therapy; international standards - Michalska, Anna; Twardowski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 1999)
The development of genetic engineering and gene therapy is much faster than progress of legislation. The international legal standards related to gene therapy (conventions, declarations and directives) are discussed and related to Polish recent situation.